Gendering platform research: Theoretical and methodological considerations. (14th May 2022) - Kampouri, Eleni
Abstract : The literature on platform labour has been growing during recent years, encompassing a wide range of themes and perspectives, including gender. Despite efforts to address gender issues in the study of platforms, however, there is still a gap in the relevant literature. This article is an attempt to address this gap by discussing some of the theoretical and methodological implications of gendering platform research. At the same time, it is an attempt to think of gender as a perspective that sheds light on the feminisation and racialisation of precarious labour more broadly and platform labour more specifically. The article explores current research strands on gender and platforms. First, it discusses how gender is and can be integrated into the collection of statistical data on platforms. Then it considers recent research on domestic and care work platforms, which constitutes an area of interest for many researchers. The concept of work-life balance in platforms is raised next and the role of reproductive and affective labour as part of platform labour. The article addresses the question of affect in platforms, especially the ways in which it can provide a valuable theoretical framework for research shedding light on the subjectivity of platform workers. Overall, the article analyses both the recent literature on the topic and possible future research directions on gender in platforms.